ANALISIS PENILAIAN KINERJA DENGAN METODE BALANCED SCORECARD PADA ORGANISASI NONPROFIT (STUDI PADA UPT PERPUSTAKAAN UNSYIAH) - MEUTHIA, FITRIZA DARA; Fahlevi, heru (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
UPT Perpustakaan Unsyiah by using balanced scorecard method and requiring the responses of the stakeholders (Head of the Unsyiah Library and Quality Assurance Staff) related to the advantages of balanced scorecard assessment in UPT Perpustakaan Unsyiah. This research uses descriptive qualitative research approach with type of case study investigation. The respondents in this study are 125 library visitors/ users, and 38 staff/ librarians. Based on the results of the study, the overall performance of Perpustakaan Unsyiah is in good criteria. Financial perspective with a score of 20, means that library financial management is effective and efficient by decreasing the cost of using the cost e-journal unit, learning and growth with a score of 19.5 means library human resources have been well developed, as well as internal business processes and customer perspectives with each each score of 19.35 means that both visitors / library users and employees / librarians are satisfied with unsyiah library services. According to the stakeholders, balanced scorecard can be used as the tool for the evaluation of Syiah Kuala University Librarys performance, because the BSC provide more informative, strongly relevant for making decision more effectively.